Wicked problems, government failures corruption and lesser evils - Ocampo, Romeo B. (2010)
Corruption is one of many tenacious problems associated with government failure. It is an example of the affinity of government -and life- with problems and failure. These are traceable to various causes or conditions, and include deficiencies and misdirections in group decision-making and in the disciplines of public administration and social science. Aside from corruption, there are other difficulties of a less morally reprehensible nature that are nonetheless wasteful and harmful and may contribute to corruption, poverty, inequality, and other "deep" problems. Issues of malfeasance deserve focal attention but should not overshadow those of misfeasance and nonfeasance. This essay attempts to maintain a balance among these concerns. After briefly discussing some aspects of corruption, it turns to the basic concepts of "wicked problems" and governmental failures and cites the results of studies that tend to substantiate their persistence in some sectors of development, including information and communication technology, automated elections, and transportation infrastructure projects abroad and in the Philippines.
Keywords: Corruption; Public services; Public works; Infrastructure (Economics)